The Impact of the Implementation of Key Audit Matters in the 2022 Independent Auditor Report of PT Bank Amar Indonesia Tbk - Auli Figa; Santy Santy; Selly Selly; Jenny Jenny (LAFADZ JAYA Publisher, 2023)
The International Auditing and Assurance Standards Board (IAASB) implemented new auditing standards which became effective on December 15, 2016, which require auditors to disclose Key Audit Matters (KAM) in their reports. KAM was initiated by the International Auditing and Assurance Standards Board (IAASB) as an international auditing standard setting body, which aims to increase the transparency of audited financial reports. This study uses qualitative and quantitative methods which use secondary data sources. The secondary data used in this study is in the form of financial reports obtained from the Indonesia Stock Exchange (IDX) via the internet. Based on the results of data analysis of the financial statements of PT Bank Amar Indonesia Tbk Q2 of 2022, in the independent auditor's report, the main audit item disclosed is the allowance for impairment losses on loans. Based on data obtained from the Indonesia Stock Exchange (IDX), the share price per share at the end of the fourth quarter of 2021 and the share price on June 30, 2022, has fluctuated. It was concluded that in the period following the issuance of the Q2 2022 financial statements with the existence of an independent auditor's report disclosing key audit matters facilitated the flow of company-specific information to the market.